Effect of supplementary zinc on orthodontic tooth movement in a rat model - Akhoundi,Mohammad Sadegh Ahmad (2016)
ABSTRACT Introduction: Osteoclasts and osteoblasts are responsible for regulating bone homeostasis during which the trace element zinc has been shown to exert a cumulative effect on bone mass by stimulating osteoblastic bone formation and inhibiting osteoclastic bone resorption. Objective: The aim of the present study was to investigate the effects of zinc (Zn) on orthodontic tooth movement (OTM) in a rat model. Material and Methods: A total of 44 male Wistar rats were divided into four groups of 11 animals each and received 0, 1.5, 20 and 50 ppm Zn in distilled water for 60 days. In the last 21 days of the study, nickel-titanium closed coil springs were ligated between maxillary right incisors and first molars of all rats, and tooth movement was measured at the end of this period. Histological analysis of hematoxylin/eosin slides was performed to assess root resorption lacunae, osteoclast number and periodontal ligament (PDL) width. Results: Mean OTM was calculated as 51.8, 49.1, 35.5 and 45 µm in the 0, 1.5, 20 and 50 ppm zinc-receiving groups, respectively. There were no significant differences in neither OTM nor histological parameters among the study groups (p > 0.05). Conclusion: According to the results obtained in the current investigation, increase in supplementary zinc up to 50 ppm does not affect the rate of OTM neither bone and root resorption in rats.